Resistance of Traditionalist Islam To the Influence of Transnational Movements Within Campus Environment - Muhsin, Ilyya; Miftahuddin, Miftahuddin; Huda, Muhammad Chairul; Ma'mun, Sukron; Wijaya, Roma (Pascasarjana IAIN Pontianak, 2025)
This study aims to analyze the efforts of traditionalist Islamic groups within Indonesian universities to counter the growing influence of transnational Islamic movements. Employing a qualitative research methodology, the study provides a comprehensive examination of the dynamics between transnational movements -such as Hizbut Tahrir Indonesia, Jamaah Tarbiyah, and Jamaah Salafi- and traditional Islamic organizations, notably Nahdlatul Ulama (NU) and the Indonesian Islamic Student Movement (PMII), within the context of the University of Yogyakarta. The findings reveal that transnational Islamic movements have strategically utilized existing campus infrastructure to expand their influence. The ideological contestation is accompanied by movement-based tensions, as traditionalist groups actively resist the growing presence of these transnational actors. The study concludes that universities play a critical role in mitigating radicalism by engaging constructively with the ideological frameworks of transnational Islamic movements.